Abnormal Calcium Metabolism Mediated Increased Risk of Cardiovascular Events Estimated by High Ankle-Brachial Index in Patients on Peritoneal Dialysis - Su, Xiaoyan; He, Wanbing; Zhang, Mengbi; Zhang, Yinyin; Zhu, Langjing; Chen, Jie; Huang, Hui (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) is the leading cause of death in peritoneal dialysis (PD) patients. But the relationship between regular PD and the risk of major adverse cardiovascular events (MACE) remains controversial. The possible risk factors are not fully elucidated. This study aims to investigate the possible factors affecting the risk of MACE estimated by high ankle-brachial index (ABI) in PD patients. A total of 243 patients were enrolled and divided into chronic kidney diseases (CKD) stage 1, non-dialyzed CKD stages 2–5, and PD groups. The prevalence of high ABI, indicating increased MACE, was elevated with CKD progression but not further increased in PD patients. Systolic blood pressure was closely correlated with high ABI in non-dialyzed CKD patients (β = 0.059, P = 0.001). But in PD patients, serum calcium had a crucial effect on high ABI (β = −9.853, P < 0.001). Additionally, PD patients with high ABI tended to dialyze inadequately (Kt/V <1.7) compared to those with normal ABI (29.0 vs. 13.3%, P = 0.031). Further mediation analysis revealed that ~86.2% of the relationship between Kt/V and high ABI was mediated by serum calcium in PD patients (mediation effect = 86.2%, ab = −0.220, 95% CI: −0.381 to −0.059, P = 0.008), especially in those starting PD before 55 years of age and with normal body mass index. This present study indicated that improvement of PD adequacy by maintaining calcium balance might be a promising method to reduce the risk of MACE estimated by high ABI for PD patients.